Mapping the Contribution of Tourism on East Java Economy: A Quadrant Analysis - Durohman, Hapid; Shofiatin, Nanik (Halal Tourism and Pilgrimage, 2024)
This study aims to map and investigate the contribution of the tourism sector to economic development in 34 regencies/cities in East Java. As one of the main drivers of economic growth, this study examines the impact of tourism across the province. Utilizing data from 2019 and 2023 provided by the Central Bureau of Statistics, this research employs a descriptive quantitative approach and analyzes various macroeconomic indicators through linear correlation analysis with a four-quadrant scatter plot. These indicators include the total Gross Regional Domestic Product (GRDP) at current prices in the accommodation and food service sector, economic growth, Gini ratio, poverty rate, and unemployment rate. This analysis aims to achieve several objectives. First, to evaluate the impact of tourism on the overall economy of East Java. Second, to investigate the role of tourism in poverty and unemployment reduction. Lastly, the study focuses on developing integrated and sustainable tourism strategies to maximize the sector's contribution to the local economy. By assessing the performance of the tourism sector and identifying existing challenges and opportunities, this research is expected to provide a solid foundation for formulating effective and optimal tourism development strategies in East Java.